Prognostic factors for the management of chondral defects of the knee and ankle joint: a systematic review - Migliorini, Filippo; Maffulli, Nicola; Eschweiler, Joerg; Goetze, Christian; Hildebrand, Frank; Betsch, Marcel (European Journal of Trauma and Emergency Surgery, 2022)
Purpose Different surgical techniques to manage cartilage defects are available, including microfracture (MFx), autologous chondrocyte implantation (ACI), osteoarticular auto- or allograft transplantation (OAT), autologous matrix-induced chondrogenesis (AMIC). This study investigated the patient-related prognostic factors on the clinical outcomes of surgically treated knee and ankle cartilage defects. Methods This study followed the PRISMA statement. In May 2022, the following databases were accessed: PubMed, Google Scholar, Embase, and Scopus. All the studies investigating the outcomes of surgical management for knee and/or talus chondral defects were accessed. Only studies performing mesenchymal stem cells transplantation, OAT, MFx, ACI, and AMIC were considered. A multiple linear model regression analysis through the Pearson Product-Moment Correlation Coefficient was used. Results Data from 184 articles (8905 procedures) were retrieved. Female sex showed a positive moderate association with visual analogue scale at last follow-up (P = 0.02). Patient age had a negative association with the American Orthopaedic Foot and Ankle Score (P = 0.04) and Lysholm Knee Scoring Scale (P = 0.03). BMI was strongly associated with graft hypertrophy (P = 0.01). Greater values of VAS at baseline negatively correlate with lower values of Tegner Activity Scale at last follow-up (P < 0.0001). Conclusion The clinical outcomes were mostly related to the patients' performance status prior surgery. A greater BMI was associated with greater rate of hypertrophy. Female sex and older age evidenced fair influence, while symptom duration prior to the surgical intervention and cartilage defect size evidenced no association with the surgical outcome. Lesion size and symptom duration did not evidence any association with the surgical outcome.
CRIS-Team WoS Importer:2022-11-25